O filme de animação O Lorax : em busca da trúfula perdida na perspectiva dos estudos culturais - Rosa, Ludmila Rodrigues (2016)
This study is included in the Education in Science and Mathematics line, in Mastership Course, Education Post-Graduate Program in Federal University of Uberlândia, Minas Gerais, Brazil. It is a research which aimed to analyze the animation film Dr. Seuss' The Lorax in order to understand which cultural issues are put into circulation from the environmental approach. We used as methodological inspiration the qualitative approach, which authorized us to find ways of representing reality and we also used the decoupage technique to better understand the movie and, as a consequence, better apprehend meanings produced by it. We analyzed it from the cultural approach, because this line includes the most varied spheres of human experience and their transformations, considering the current context and singularities. Therefore, we seek to understand in what way the cinema, more specifically the animated film artifact, according to cultural studies method, materializes social culture, act as a knowledge producer and builds important meanings in the formation of historical, social and cultural subjects. The film analysis allowed us to perceive that subjects, society and nature are symbolized in the it by the way the characters are presented in the story and how they set their own figurations, as well how the main tools are used in building the cultural subject. The research relevance focuses on the breakdown of using the film only as entertainment, because it allows us a more conscious access to our inner life and, consequently, with our own learning, so it is a pedagogic dispositive that leverages new knowledge. Therefore vision is not merely a skill but a cultural construction that learns and teaches within the social practices, forming identities.